2004
DOI: 10.1007/s10238-004-0049-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of interleukin-10 in saliva of Sjögren’s syndrome patients. Correlation with disease activity

Abstract: The aim of the study was to determine the levels of interleukin (IL)-10, IL-2, IL-4, and interferon-gamma in the saliva of patients with Sjögren's syndrome and to correlate them with laboratory and clinical parameters of disease activity. The levels of IL-2, IL-4, IL-10, and interferon-gamma were measured in salivary samples, obtained directly from the Stenone duct of 14 Sjögren's syndrome patients and 26 healthy controls by ELISA. A significant elevation of IL-10 was found in salivary fluids of Sjögren's synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 16 publications
6
21
1
1
Order By: Relevance
“…One possible mechanism for autoimmune exocrinopathy is altered T helper differentiation and cytokine production (7). Interestingly, the pattern of cytokines we observe in PI3K-deficient CD4 ϩ T cells after Th2 polarization (increased IFN-␥ and IL-10, decreased IL-4) is similar to the unusual pattern observed in saliva and T cell clones from SS patients (21)(22)(23). IFN-␥ induces B cell activating factor of the TNF family (BAFF) and chemokine expression by salivary gland epithelial cells (24,25); this suggests that aberrant cytokine production may play a pivotal role in disease progression.…”
Section: Discussionsupporting
confidence: 81%
“…One possible mechanism for autoimmune exocrinopathy is altered T helper differentiation and cytokine production (7). Interestingly, the pattern of cytokines we observe in PI3K-deficient CD4 ϩ T cells after Th2 polarization (increased IFN-␥ and IL-10, decreased IL-4) is similar to the unusual pattern observed in saliva and T cell clones from SS patients (21)(22)(23). IFN-␥ induces B cell activating factor of the TNF family (BAFF) and chemokine expression by salivary gland epithelial cells (24,25); this suggests that aberrant cytokine production may play a pivotal role in disease progression.…”
Section: Discussionsupporting
confidence: 81%
“…In the current study, the production of IL-4 was not observed in the lacrimal glands of NOD/LtJ mice in all groups, suggesting that IL-4 may be more required to regulate the B-cell autoimmune response in this animal model. IL-10 is a cytokine capable of inhibiting the synthesis of other proinflammatory cytokines, but the secretion of IL-10 has also been shown to be elevated in patients with SS [29, 30]. However, no changes in the concentration of IL-10 were observed in the current study, suggesting that IL-10 may not be regulated following immunization with M3R 208–227 .…”
Section: Discussioncontrasting
confidence: 61%
“…In some autoimmune cases, however, reduction of the Th1 response or a Th2 type shift may alleviate disease; many apparent exceptions are now well documented. And Th2-derived cytokines such as IL-10 have been found to be elevated in the saliva of Sjogren's syndrome patients and correlate with the severity of the disease [17]. The results of Mitsias and his colleagues reported that Type II microenvironment prevails in low-grade infiltration, while type I pattern increases in patients with definite SS, and patients with advanced lymphocytic infiltration may suggest that the cytokine pattern may shift from Th1 to Th2 as the immunopathological lesions progress [18].…”
Section: T Cellsmentioning
confidence: 99%